A comprehensive sintering mechanism for thermal barrier coatings‐Part III: Substrate constraint effect on healing of 2D pores. Issue 8 (28th February 2018) - Li, Guangrong; Yang, Guanjun; Li, Chengxin; Li, Changjiu
Abstract: During thermal exposure, the sintering of the plasma‐sprayed thermal barrier coatings (PS‐TBCs) is highly dependent on the healing of the two‐dimensional (2D) pores (including the inter‐splat pores and the intra‐splat cracks), as reported in the previous Part‐I and Part‐II based on free‐standing coatings. As a further study, this part aims to reveal the effect of substrate constraint on healing behavior of the 2D pores, since the coatings are actually bonded to superalloy substrate during real service. The healing of the 2D pores was quantitatively examined, and the multiscale mechanical properties were determined during the overall thermal exposure. In addition, a structure model was used to quantitatively correlate the evolution of 2D pores with mechanical property. The results of experiments and model prediction show that, different from the two‐stage evolutionary trends in free‐standing coatings, the overall evolution trends of microstructure and property can be divided into 3 stages affected by the substrate constraint. Moreover, the anisotropic healing of the 2D pores reported in free‐standing coatings was enhanced significantly due to the additional stress in coatings resulting from constraint of substrate. This means that the healing of inter‐splat pores became faster and severer. Given that, an outlook on structural tailoring to retard the performance degradation of TBCs was proposed.